Combined therapy in metabolic syndrome treatment - Yu. V. Zhernakova; V. B. Mychka; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
According to the latest recommendations by the European Society of Hypertension and the European Society of Cardiology, in patients with high cardiovascular risk (including individuals with diabetes mellitus and metabolic syndrome), the first-choice agents for arterial hypertension (AH) treatment are combined medications. Ideally, one medication should combine blockers of renin-angiotensin system and a metabolically neutral diuretic. The combined medication Noliprel A fulfils these requirements, being a fixed low-dose combination of ACE inhibitor perindopril arginine and thiazide-like diuretic indapamide. Noliprel A demonstrates not only good antihypertensive effects, but also beneficial metabolic and organo-protective activity. Therefore, it can be recommended as firstchoice medication in this clinical group.